2013
DOI: 10.1016/j.chom.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

HRas Signal Transduction Promotes Hepatitis C Virus Cell Entry by Triggering Assembly of the Host Tetraspanin Receptor Complex

Abstract: Hepatitis C virus (HCV) entry is dependent on coreceptor complex formation between the tetraspanin superfamily member CD81 and the tight junction protein claudin-1 (CLDN1) on the host cell membrane. The receptor tyrosine kinase EGFR acts as a cofactor for HCV entry by promoting CD81-CLDN1 complex formation via unknown mechanisms. We identify the GTPase HRas, activated downstream of EGFR signaling, as a key host signal transducer for EGFR-mediated HCV entry. Proteomic analysis revealed that HRas associates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
194
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 148 publications
(205 citation statements)
references
References 52 publications
8
194
2
1
Order By: Relevance
“…Multiple lines of evidence support a critical role for EGFR in HCV entry (38). Binding of HCVcc particles to cells induces EGFR activation (75), EGFR ligands enhance HCV entry (38,75), and EGFR/HRas signaling promotes CD81-CLDN1 binding (41). Moreover, EGFR ligands were shown to increase colocalization of EGFR with CD81 and their localization to early endosomes, suggesting a potential role for EGFR in a step following CD81-CLDN1 engagement (75).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple lines of evidence support a critical role for EGFR in HCV entry (38). Binding of HCVcc particles to cells induces EGFR activation (75), EGFR ligands enhance HCV entry (38,75), and EGFR/HRas signaling promotes CD81-CLDN1 binding (41). Moreover, EGFR ligands were shown to increase colocalization of EGFR with CD81 and their localization to early endosomes, suggesting a potential role for EGFR in a step following CD81-CLDN1 engagement (75).…”
mentioning
confidence: 99%
“…Additional cellular molecules identified as HCV entry factors include the two receptor tyrosine kinases epidermal growth factor receptor (EGFR) and ephrin type A receptor 2 (EPHA2) (38), the cholesterol uptake molecule Niemann-Pick C1-like 1 (NPC1L1) (39), and transferrin receptor 1 (TFR1) (40). CD81-bound HCV particles have been shown to traffic laterally on the plasma membrane to tight junctions, where they form stable CD81-CLDN1 complexes, and these activities are promoted by protein kinase A (PKA), Rho, and EGFR/HRas signaling (38,(41)(42)(43)(44). Multiple lines of evidence support the finding that HCVpp and HCVcc enter the cell via clathrin-mediated endocytosis (13,(45)(46)(47)(48)(49).…”
mentioning
confidence: 99%
“…Besides its dipeptidase function, PEPD has been shown to be involved in epidermal growth factor receptor (EGFR) family signaling (37,38). EGFR signaling is believed to play a role during IAV infections (39,40). In addition, gene ontology analysis of the validated hits of the siRNA screens revealed that kinase signaling is the most overrepresented category (31).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo treatment of erlotinib resulted in a significant suppression of the viral load in PHH-chimeric mouse model with HCV infection [54]. Furthermore, inhibitors of EGFR downstream kinases Ras (tipifarnib) and Raf (sorafenib) were also assessed and found effective in blocking HCV entry [126].…”
Section: Small Molecules Targeting Host Entry Factors and Cd81-triggementioning
confidence: 99%